THE CURRENT AND FUTURE ENERGY ECONOMICS OF CONCENTRATING SOLAR POWER (CSP) IN SOUTH AFRICA - Craig, O O; Brent, Alan; Dinter, Frank (The South African Journal of Industrial Engineering, 2017)
For South Africa, an increase in energy demand is associated with higher CO2 emissions. In order to overcome this challenge, the government started the Renewable Energy Independent Power Producer Procurement Programme (REI4P) to allow easy integration of renewable energy technologies into the existing energy mix. The country has an abundant solar resource, and the potential to harvest this resource through concentrating solar power (CSP) has been proven. 600 MW of CSP have been bought in the REI4P, but the future of CSP in SA looks bleak, as the government’s recent Integrated Resource Plan (IRP) updates gave no allocation to new CSP plants beyond 2030. Very few CSP plants are connected to the grid, and there is limited research and literature on its learning effect and economics of scale. This study analyses the state of CSP and uses a mathematical relationship to determine the progress ratio, the learning effect, and the likely future of CSP in South Africa. The results address the difficulties involved in determining the learning effect of CSP.